THE POTENTIAL OF DIGITAL TECHNOLOGIES IN IMPROVING THE PROCESS OF TRAINING AND RETRAINING OF MILITARY DOCTORS - Тетяна Галкіна; Віра Андрієвська (Institute of Pedagogy of NAES, 2024)
The issue of improving the process of training and retraining of military doctors is determined by changes in the security environment of the state today, and the need to develop the military medical sector in the conditions of long-term resistance to russian aggression. This article highlights the potential of using digital technologies to improve the process of training and retraining of military doctors. The results of a survey of trainees at the Ukrainian Military Medical Academy (a higher military medical educational institution that provides training, retraining and advanced training of specialists in almost all specialties for the Armed Forces of Ukraine and other military establishment of Ukraine) are presented. It is shown that for the implementation of changes in the system of training and retraining of military doctors the Academy provides for a number of measures: introducing innovative changes in the content and methodology of education; introduction of flexible technology for planning and organizing the educational process, focused on personalization of learning; development of international scientific and scientific-medical collaborations. Based on the conducted research, it was determined that in the conditions of active hostilities in Ukraine, it is digital technologies that make it possible to quickly introduce changes in the process of training and retraining of military doctors by improving the educational and informational environment. It was established that improving the readiness of military doctors to use digital technologies in their professional activities requires their end-to-end use in the entire training system. The article provides examples of the use of digital technologies in the process of training and retraining of military doctors.